Symmetry in designs clothing fabrics: تيجانية عدنان عبد الرحمن (Al-Academy, 2015)
The art of designing clothing fabrics is a multidisciplinary design important and difficult because it is linked to man and his personality and his tastes and habits and behavior being is a form of creative expression here came the problem of the research , which are summarized by asking the following: Is the similar role in the designs of clothing fabrics The second chapter included two themes design fabrics the symmetry in the design of fabrics the third chapter included research procedures adopted descriptive analytical method to reach the goals of the research and consisted of the research community (9) models of the designs fabrics Iraqi either the research sample was selected (5) models of society current search and search tool Vtmthelt set of axes basic theoretical framework was derived from either the most important results that have emerged through research are1 - afternoon he has not been achieved as a result of symmetry match elements are monotonous , but alternately in all samples design which added a kind of change that ease the monotony .The most important conclusions :1 - has been associated with symmetry Bassas balance ( symmetric and asymmetric ) designs in fabrics Almbusah in most of the samples examined, and devoid of the adoption of the radiation balance Awahar who lend a distinctive diverse vocabulary in the distribution of replica